A New Look at the Longitudinal Relationship Between Motor Carrier Financial Performance and Safety. Issue 3 (30th August 2016) - Miller, Jason W.; Saldanha, John P.
Abstract : Motor carrier safety impacts the well‐being of the traveling public and the economic well‐being of the shippers who entrust motor carriers with safely transporting freight. Shippers are affected by motor carrier safety due to accidents damaging their cargo and disrupting their customers' operations. One characteristic frequently theorized to predict motor carrier safety is motor carriers financial performance. However, the literature offers mixed evidence linking motor carrier financial performance to safety. This does not help practitioners or policy makers and necessitates research to resolve these inconsistent findings, which we undertake in this research. We extend previous work by developing a theoretical framework based on strain theory to explain why both absolute (static) financial performance and year‐to‐year change in financial performance should uniquely affect carrier safety. We test our hypotheses by fitting mixed‐effects models to a repeated‐measure, longitudinal database of publically traded motor carrier financial performance and safety measures. Results indicate that financial performance measures uniquely affect carrier safety. These findings attempt to resolve the inconsistencies in the past literature and, carry important implications for researchers studying motor carrier safety, motor carrier managers, shippers, and policy makers.